2007
DOI: 10.1002/hbm.20269
|View full text |Cite
|
Sign up to set email alerts
|

Effect of syntactic similarity on cortical activation during second language processing: A comparison of English and Japanese among native Korean trilinguals

Abstract: In this study of native Korean trilinguals we examined the effect of syntactic similarity between first (L1) and second (L2) languages on cortical activation during the processing of Japanese and English, which are, respectively, very similar to and different from Korean. Subjects had equivalent proficiency in Japanese and English. They performed auditory sentence comprehension tasks in Korean, Japanese, and English during functional MRI (fMRI). The bilateral superior temporal cortex was activated during the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 38 publications
4
40
0
Order By: Relevance
“…To provide a more detailed analysis, we divided the IFG into three sub-regions [pars opercularis (IFGop), pars triangularis (IFGpt), and pars orbitalis (IFGor)], the posterior parietal cortex into three sub-regions [supramarginal gyrus (SMG), angular gyrus (AG), and superior parietal lobule (SPL)], leading to a total of 12 ROIs in the left hemisphere. The selection of the 12 ROIs are also consistent with other previous studies (Hernandez & Li, 2007; Jeong et al, 2007; Mechelli et al, 2004). Functionally, it has been generally accepted that more extensive left hemisphere activations are associated with bilinguals than monolinguals especially in late bilinguals and low proficiency bilinguals.…”
Section: Introductionsupporting
confidence: 91%
“…To provide a more detailed analysis, we divided the IFG into three sub-regions [pars opercularis (IFGop), pars triangularis (IFGpt), and pars orbitalis (IFGor)], the posterior parietal cortex into three sub-regions [supramarginal gyrus (SMG), angular gyrus (AG), and superior parietal lobule (SPL)], leading to a total of 12 ROIs in the left hemisphere. The selection of the 12 ROIs are also consistent with other previous studies (Hernandez & Li, 2007; Jeong et al, 2007; Mechelli et al, 2004). Functionally, it has been generally accepted that more extensive left hemisphere activations are associated with bilinguals than monolinguals especially in late bilinguals and low proficiency bilinguals.…”
Section: Introductionsupporting
confidence: 91%
“…Note: Studies with multiple tasks were used more than once in data analysis (e.g., Buchweitz et al, 2012). b Participants' mean age was not reported in the following studies, where the minimal and maximal ages were averaged as the mean age (Chan et al, 2008;Chee et al, 2001;De Bleser and Kauschke, 2003;Golestani et al, 2006;Huang et al, 2012;Jeong, Sugiura, Sassa, Haji, et al, 2007;Luke et al, 2002;Nakamura et al, 2010;Perani et al, 1998Perani et al, , 2003Rao et al, 2013;Tan et al, 2003;Tham Wei Ping, 2003;Wang et al, 2010). …”
Section: The Effect Of L2 Aoa On L1 Activationmentioning
confidence: 99%
“…So far, many studies have investigated brain activities of bilinguals involved in the processing of L1 and L2, and as summarized by Indefrey (2006) and Abutalebi (2008), differences between L1 and L2 are usually reflected at the brain level by more extended activation patterns of L2 within or surrounding those regions responsible for L1 processing. As to why L2 engages more widespread brain activity, several studies have also suggested that the brain activity for language processing is modulated by specific demographic, linguistic and/or behavioral variables, such as language exposure in daily life Jeong et al, 2007;Perani et al, 2003), proficiency level (PL) (Briellmann et al, 2004;Chee, Caplan, et al, 1999;Frenck-Mestre, Anton, Roth, Vaid, & Viallet, 2005;Gandour et al, 2007;Golestani et al, 2006;Illes et al, 1999;Kotz, 2009;Perani et al, 1996Perani et al, , 1998, age-of-acquisition (AoA) of L2 (Bloch et al, 2009;Dehaene et al, 1997;Hernandez, Hofmann, & Kotz, 2007;Kim, Relkin, Lee, & Hirsch, 1997;Mayberry, Chen, Witcher, & Klein, 2011;Perani et al, 2003;Wartenburger et al, 2003), cross-linguistic similarities/dissimilarities (Jeong et al, 2007;Saur et al, 2009), and syntactic complexity (Suh et al, 2007;Yokoyama et al, 2006). Following Abutalebi and Green (2007), the extra-activity of L2 would be induced by an apparent lack of automaticity such as in cases where the proficiency for L2 is low or, likewise, when L2 is learnt later in life.…”
Section: Introductionmentioning
confidence: 99%
“…Language exposure was by then hypothesized to predict language outcome in bilingual aphasia, in the sense that the language the patient used more prior to the brain insult, was the one with the highest possibilities for recovery (see for discussion in . To the best of our knowledge, only very few functional neuroimaging studies have analyzed the effects of language exposure upon the cerebral representation of languages in bilinguals Jeong et al, 2007;Perani et al, 2003). For example, Perani et al (2003) carried out an fMRI study in high proficient Catalan-Spanish early bilinguals performing a lexical search and retrieval task, and found additional brain activity in the left middle frontal gyrus (MFG) (BAs 10, 46) and left inferior parietal lobule (IPL) (BA 40) only for the L2 to which subjects were less used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation